Preliminary Studies of the Effect of Phosphatic Fertilizers on Forage Yield and Root Development of Grasses - Puri, D N; Khyabri, M L; Paliwal, M K; Singh, Takhat (Annals of Arid Zone, 2016)
Studies on the effect of phosphate application on root weight, root diameter, forage yield and binding capacity were made, in the case of two grasses, viz. Dichanthium annlulatum and Cenchrus ciliaris. Root weight and binding factor significantly increased with the application of 40 kg. P205/ha. upto 30 cm depth. Binding factor increased by 66% in case of Dichanthium allnulatum and 87% in case Cenchrus ciliaris. Though effect of phosphate on forage yield was not significant, yet there was increase in the yield of grass at P40 level. In order to increase the binding capacity of the grasses, application of 40 kg. P205/ha. is beneficial.